Studi Tingkat Kekeringan Meteorologis Di Kecamatan Air Majunto Kabupaten Muko-Muko - Supriyanto Supriyanto; Nofirman Nofirman; Zairin Zairin (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2016)
The purpose of this study was to determine the distribution and severity of droughts meteorological Water District Majunto Muko-Muko. The approach used in this study using quantitative descriptive. The population in this study is seluh duration or range that is in the District of Air Majunto Muko-Muko. Sampael in this study using rainfall data from 2008 to 2015. Engineering Technical analysis of data used in the study using the SPI (Standardized Precipitation Index). the following results: (1) Distribution of drought meteorological Water District Majunto Muko-Muko from 2008 to 2015 dry days highest dominance in May 2008, March, June and July of 2009, in August and September in 2011, and in September 2012. Today dried'm much dominance in January of 2008, in April and in August 2009, January, May, and July of 2011, in May 2012, March 2013, the month August 2014, June, July 2015 and (2) Degree of meteorological drought Water District Majunto Muko-Muko from 2008 to 2015 drought levels extremely dry much dominance in 2009 and 2012.